Expansion of MyDispense: A Descriptive Report of Simulation Activities and Assessment in a Certified Pharmacy Technician Training Program - Cassandra R. Doyno; Lisa M. Holle; Renee Puente; Sharee Parker; Lauren M. Caldas; Barbara Exum (MDPI AG, 2023)
Background: Yale New Haven Health (YNHH) implemented a pharmacy technician training program in 2016. The curriculum includes 14 weeks of combined didactic and simulation hours (280 h in total), followed by 360 h of experiential learning. MyDispense, an online pharmacy simulation, allows students to develop and practice their dispensing skills in a safe environment with minimal consequences for mistakes. We describe a novel innovation, expanding the functionality of MyDispense to the training of pharmacy technicians. Methods: Technician training coordinator, supervisor, faculty members with experience in MyDispense, and experiential pharmacy students created cases within the MyDispense software that were targeted towards pharmacy technician activities. Activities were aligned with current American Society of Health-System Pharmacists (ASHP)-Accreditation Council for Pharmacy Education (ACPE) Accreditation Standards for pharmacy technician education and training programs. Results: A total of 14 cases were developed to be utilized in student technician training, and account for approximately 14 h of simulation. Conclusions: MyDispense is an innovative software that could allow students to access and complete exercises, and to continue developing dispensing skills in a safe, remote environment. We identified similarities between activities performed by student pharmacists and student pharmacy technicians, expanding MyDispense to a new learner group to practice, develop and be assessed on dispensing skills within their scope, as part of a formal technician training program and in preparation for the Pharmacy Technician Certification Examination (PTCE).